The Compressibility of pH‐Sensitive Microgels at the Oil–Water Interface: Higher Charge Leads to Less Repulsion1. (28th March 2014) - Geisel, Karen; Isa, Lucio; Richtering, Walter
Abstract pH‐responsive microgels are unique stabilizers for stimuli‐sensitive emulsions that can be broken on demand by changing the pH value. However, recent experiments have indicated that electrostatic interactions play a different role to that in conventional Pickering emulsions. The influence of charges on the interactions between microgels at the oil–water interface is now described. Compression isotherms of microgels with different charge density and architecture were determined in a Langmuir trough, and counter‐intuitive results were obtained: Charged microgels can be compressed more easily than uncharged microgels. The compressibility of microgels is thus not determined by direct Coulomb repulsion. Instead, the different swelling of the microgels in the charged and the uncharged states is proposed to be the key parameter.